Application of the Interim Accord of 13 September 1995. (2016) - Unknown
Abstract : 476 International organizations — Membership — Admission of new members — United Nations — NATO — Name by which Member State to be known — Admission of State with provisional name — The former Yugoslav Republic of Macedonia — United Nations Security Council resolution 817 (1993) — United Nations Security Council resolution 845 (1993) — Negotiations regarding name — Interim Accord with Greece — Undertaking by Greece not to oppose admission of State to international organizations — Undertaking not applicable if State to be referred to in organization differently than in resolution 817 (1993) — State describing itself as Macedonia — NATO admission of new members by consensus — Whether Greece opposed admission — Whether violation of Interim Accord International Court of Justice — Jurisdiction — Interim Accord between Greece and State referred to in United Nations as the former Yugoslav Republic of Macedonia — Provision for reference of disputes to International Court of Justice — Scope of jurisdiction — Admissibility — Whether Court required to rule on conduct of NATO — Whether judicial proceedings likely to prejudice diplomatic negotiations States — New State — Socialist Federal Republic of Yugoslavia — Dissolution — Declaration of independence by Socialist Republic of Macedonia — Name of new State — Admission of new State to United Nations as the former Yugoslav Republic of Macedonia — Interim Accord with Greece — State referring to itself as the Republic of Macedonia Treaties — Interpretation — Plain meaning of text — Object and purpose of treaty — Context of provision — Subsequent practice of parties as guide to interpretation — Breach — Remedies — Material breach — Countermeasures — Exceptio non adimpleti contractus — Whether forming part of contemporary international law